On recent results in the modelling of neoclassical-tearing-mode stabilization via electron cyclotron current drive and their impact on the design of the upper EC launcher for ITER. (5th January 2015) - Poli, E.; Angioni, C.; Casson, F.J.; Farina, D.; Figini, L.; Goodman, T.P.; Maj, O.; Sauter, O.; Weber, H.; Zohm, H.; Saibene, G.; Henderson, M.A.
Abstract: Electron cyclotron wave beams injected from a launcher placed in the upper part of the vessel will be used in ITER to control MHD instabilities, in particular neoclassical tearing modes (NTMs). Simplified NTM stabilization criteria have been used in the past to guide the optimization of the launcher. Their derivation is reviewed in this paper and their range of applicability clarified. Moreover, possible effects leading to a deterioration of the predicted performance are discussed. Particularly critical in this context is the broadening of the electron-cyclotron (EC) deposition profiles. It is argued that the most detrimental effect for ITER is likely to be the scattering of the EC beams from density fluctuations due to plasma turbulence, resulting in a beam broadening by about a factor of two. The combined impact of these effects with that of beam misalignment (with respect to the targeted surface) is investigated by solving the Rutherford equation in a form that retains the most relevant terms. The perspectives for NTM stabilization in the Q = 10 ITER scenario are discussed.